US Relations with South Asia (Since Christopher Columbus) and Pakistan-India Interaction, 1492-2002 - Afrasiab (Islamabad WordMate, 2002)
Events pertaining to relations among Pakistan, United States and India, from 1492 to 2002, chronologically arranged with brief descriptions.
Keywords: South Asia -- Foreign Relations -- United States -- Chronology -- United States -- Foreign Relations -- South Asia -- Chronology -- India -- Foreign Relations -- Pakistan -- Chronology